Autonomous collection of ground truth data by unmanned aerial vehicles instructed using SMS text messages - Williamson, Alex A.; Mondal, Sabyasachi; Xu, Zhengjia; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2020)
This paper describes a solution to increase the efficiency of collecting agricultural ground truth data by the use of one or more off-the-shelf drones to autonomously collect high quality RGB image data at low level, through the incorporation of a bespoke smartphone application that receives routing path-planned location data in the form of Short Message Service (SMS) text messages.
Keywords: Android Application; Autonomous ground truth